HUBUNGAN LINGKUNGAN SEKOLAH DAN TINGKAT PENGETAHUAN SISWA SD KELAS IV-VI DENGAN CARA MENCUCI TANGAN TERHADAP KEJADIAN DIARE DI SDN 10 TALIWANG - Wiwik Sari Aprianturi; Dewi Utary; Nadira Yumna; Sabariah (Nusantara Hasana Journal, 2023)
Background: Diarrhea is a condition where bowel movements are soft or liquid, in the form of water, more frequently (usually three times or more) in one day. Poor personal hygiene behavior can make a person susceptible to diseases such as diarrhea, this condition contributes to the high incidence of diarrhea in Indonesia. Improper hand washing behavior is still high found in children aged 10 years and over above about 67.4%.This shows that the lack of knowledge about hand hygiene, the condition of hands that are not clean, contaminated food, resulting in infection (bacteria, viruses, parasites), malabsorption, food poisoning and behavior of unhygienic snacks. Research purposes: To find out the relationship between the school environment and the level of knowledge about how to wash hands of SD students in grades IVVI on the incidence of diarrhea at SDN 10 Taliwang Research methods: Observational analytic research with cross sectional research design. The sampling technique used starified random sampling. The research was conducted at SDN 10 Taliwang in August-September 2022. The research sample was 70 respondents. The data obtained were analyzed by Chi Square test. The significance value limit is (p≤0.05). Research result : The study showed that of the 70 respondents, students who did not experience diarrhea with a healthy environment were 58 respondents (82.9%). The results of the bivariate analysis show that the valuep-values< 0.05 (p-values= 0.00). PR values obtained in this study PR > 1 (PR + 3.00) (95% CI = 1.35 - 6.68). Based on the variable level of knowledge of hand washing, from 70 respondents, it was found that students who did not experience diarrhea with a good level of knowledge were 54 respondents (77.1%). The results of the bivariate analysis show that the valuep-values< 0.05 (p-values= 0.00). The description of the observation results obtained 60 respondents (85.7%) who carried out appropriate hand washing actions based on the Indonesian Ministry of Health. Conclusion : There is a significant relationship between the school environment and the level of knowledge about how to wash hands of SD students in grades IVVI on the incidence of diarrhea at SDN 10 Taliwang.